Carbon Nanotube Fabric Cooling System for Firefighters and First Responders: Modeling and Simulation (Journal of Fiber Bioengineering and Informatics, 2015)
This study investigates carbon nanotube textiles as advanced personal protection equipment for\rfirefighters and first responders. Carbon nanotubes are lightweight, flame resistant, and possess high\rmechanical and thermal properties. Carbon nanotubes are also thermally anisotropic, meaning they\reasily conduct heat along the axis of an individual tube, and are relatively insulating across the tube's\rdiameter. By recognizing this anisotropic behavior, heat transfer through a layer of aligned carbon\rnanotubes in a garment can be partially redirected to a cold reservoir thereby protecting the wearer\rfrom heat stress and exhaustion. Finite element models were developed to simulate a carbon nanotube\rlayer embedded in a firefighting garment and thermally connected to a cold reservoir. Simulation showed\rthat under heat stress conditions, firefighter skin temperature was considerably reduced by the cooling\rlayer.
Keywords: Firefighter; Personal Protection; Carbon Nanotube Textile; Cooling